THE INFLUENCE OF ARM LENGTH, VO2 MAX AND CORE STABILITY ON ARROW SKILLS - Rabbani, Rifqi; Junaidi; Susilo (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The purpose of this study was to determine the relationship between arm length, VO2 Max and Core stability on archery skills. A total of 24 athletes of KOP Archery Fortius, State University of Jakarta who became the research subjects. Measurement of research results using anthropometric measurement instruments of arm length, running multistage fitness test (Balke test) , plank and shooting 3 arrows for 10 series and 2 sessions with the highest total score of 600 with a distance of 18 meters. Analysis of research data using path analysis technique. Based on the results of this study, it was explained that the seven research hypotheses were accepted. H1: There is a direct effect of arm length (X1) on archery skills (Y). H2: There is a direct effect of VO2 Max (X2) on archery skills (Y). H3: There is a direct effect of Core stability (X3) on archery skills (Y). H4: There is a direct effect of arm length (X1) on Core stability (X3). H5: There is a direct effect of VO2 Max (X2) on Core stability (X3). H6: There is a direct effect of arm length (X1) on archery skills (Y) through Core stability (X3). H7: There is a direct effect of VO2 Max (X2) on archery skills (Y) through Core stability (X3).